Treatment Patterns, Depression, and Anxiety Among US Patients Diagnosed with Hyperhidrosis: A Retrospective Cohort Study - Stephanie Z. Klein; Michael Hull; Kristin Khalaf Gillard; Jesse Peterson-Brandt (Adis, Springer Healthcare, 2020)
Abstract Introduction Hyperhidrosis is associated with social and emotional stress due to limitations on health-related quality of life. This study examined real-world treatment patterns and concomitant depression and/or anxiety in patients with hyperhidrosis. Methods Commercial health plan members in the US with ≥ 2 hyperhidrosis diagnosis codes and/or antiperspirant prescription claims were identified from January 2010 through November 2017. A control cohort (CC) of patients without hyperhidrosis was matched to the hyperhidrosis cohort on demographic characteristics. Depression and/or anxiety were identified by ≥ 1 relevant diagnosis code or pharmacy claim. A multivariable logistic regression model estimated odds of treatment in the hyperhidrosis cohort, and depression/anxiety in the hyperhidrosis cohort and CC, adjusting for patient characteristics. Results A total of 44,484 patients with hyperhidrosis were identified, of whom 58.5% were female, with a mean (± standard deviation) age of 36.5 ± 16.5 years (83.5% ≥ 18 years). A small majority of patients (51.6%, 0.69/person-year) received treatment with prescription antiperspirants. Post-index oral systemic therapies, medical procedures, and surgical options were uncommon. At 12 months post-index, 48.4% of the sample had not filled a prescription for extra- or prescription-strength antiperspirants. Compared with the CC (n = 137,451), a higher percentage of patients with hyperhidrosis had depression or anxiety reported during follow-up (41.1 vs. 28.2%, p < 0.001); this corresponded to higher adjusted odds of depression/anxiety in patients with hyperhidrosis [odds ratio (OR) 1.76, 95% confidence interval (CI) 1.72-1.80, p < 0.001]. Baseline depression and/or anxiety were associated with lower odds of receiving hyperhidrosis treatment (OR 0.77, 95% CI 0.73-0.80), as was increasing age and male gender. Patients with hyperhidrosis also had more frequent incident depression/anxiety during follow-up (18.2 vs. 10.6%, p < 0.001). Conclusion In this real-world analysis, hyperhidrosis was associated with increased odds of depression and/or anxiety. However, relatively low percentages of patients received prescription topical or oral treatments or underwent surgery, suggesting that tolerability, efficacy, and provider awareness may be limiting factors in the effective treatment of hyperhidrosis.